STRATEGI PEMBERDAYAAN MASYARAKAT DESA LASIWALA KABUPATEN SIDENRENG RAPPANG DALAM MENINGKATKAN KEMANDIRIAN EKONOMI BERBASIS SUMBER DAYA LOKAL MELALUI BUMDES - Maya Alfinia; Ahmad Mustanir; Barisan; Herman Dema (LPPM Universitas Abdurrab, 2025)
This study aims to identify the management model of Village-Owned Enterprises (BUMDes) and community empowerment strategies in enhancing local resource-based economic independence in Lasiwala Village, Sidenreng Rappang District, South Sulawesi, by 2025. The issues addressed are how to establish an effective BUMDes management model and how community empowerment strategies are implemented to support village development. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. Informants consist of village officials, BUMDes administrators, and local residents. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results indicate that the BUMDes management model applies the principles of cooperation, participation, emancipation, transparency, accountability, and sustainability, although its implementation is not yet optimal. Community empowerment strategies are implemented collaboratively through village deliberations and community involvement in program management, supported by APBDes funds and community participation. Despite logistical challenges, the implementation process reflects democratic and responsive governance. Findings also indicate that this strategy is quite effective in increasing participation, access, and community business development. However, it is necessary to strengthen financial literacy, business unit innovation, and more systematic evaluation so that the impact of empowerment can be more sustainable. The practical implication of this research is that strengthening managerial capacity and broader community involvement are essential to achieving economic sustainability based on local resources.